Severe Primary Hyperparathyroidism Caused by Parathyroid Carcinoma in a 13‐Year‐Old Child; Novel Findings From HRpQCT. (2nd January 2020) - Lenherr‐Taube, Nina; Lam, Carol KL; Vali, Reza; Shammas, Amer; Campisi, Paolo; Zawawi, Faisal; Somers, Gino R; Stimec, Jennifer; Mete, Ozgur; Wong, Andy KO; Sochett, Etienne
ABSTRACT: Primary hyperparathyroidism is a condition that occurs infrequently in children. Parathyroid carcinoma, as the underlying cause of hyperparathyroidism in this age group, is extraordinarily rare, with only a few cases reported in the literature. We present a 13‐year‐old boy with musculoskeletal pain who was found to have brown tumors from primary hyperparathyroidism caused by parafibromin‐immunodeficient parathyroid carcinoma. Our patient had no clinical, biochemical, or radiographic evidence of pituitary adenomas, pancreatic tumors, thyroid tumors, pheochromocytoma, jaw tumors, renal abnormalities, or testicular lesions. Germline testing for AP2S1, CASR, CDC73/HRPT2, CDKN1B, GNA11, MEN1, PTH1R, RET, and the GCM2 gene showed no pathological variants, and a microarray of CDC73/HRPT2 did not reveal deletion or duplication. He was managed with i.v. fluids, calcitonin, pamidronate, and denosumab prior to surgery to stabilize hypercalcemia. After removal of a single parathyroid tumor, he developed severe hungry bone syndrome and required 3 weeks of continuous i.v. calcium infusion, in addition to oral calcium and activated vitamin D. Histopathological examination identified an angioinvasive parathyroid carcinoma with global loss of parafibromin (protein encoded by CDC73/HRPT2 ) . HRpQCT and DXA studies were obtained prior to surgery and 18‐months postsurgery. HRpQCT showed a resolution of osteolytic lesions combined with structural improvement of cortical porosity and an increase in both cortical thickness and density compared with levels prior to treatment. These findings highlight the added value of HRpQCT in primary hyperparathyroidism. In addition to our case, we have provided a review of the published cases of parathyroid cancer in children. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.